Normal alkaline phosphatase in primary biliary cirrhosis. Issue 630 (April 1978) - Leslie, D.
Abstract : A patient with primary biliary cirrhosis is described. Throughout her illness the serum alkaline phosphatase remained normal and this unique feature emphasizes the importance of histology in diagnosing the disease.